Proceedings of the ACM Symposium on Document Engineering 2019 2019
DOI: 10.1145/3342558.3345393
|View full text |Cite
|
Sign up to set email alerts
|

Using Knowledge Base Semantics in Context-Aware Entity Linking

Abstract: Entity linking is a core task in textual document processing, which consists in identifying the entities of a knowledge base (KB) that are mentioned in a text. Approaches in the literature consider either independent linking of individual mentions or collective linking of all mentions. Regardless of this distinction, most approaches rely on the Wikipedia encyclopedic KB in order to improve the linking quality, by exploiting its entity descriptions (web pages) or its entity interconnections (hyperlink graph of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…For NERC, they improved the non-neural CRF baseline system with additional features such as context tokens, date regex match, ASCII normalization of the focus token, and the 100 most similar words from the HIPE fastText word embeddings provided by the organizers. For EL, a knowledge-base driven approach was applied to disambiguate and link the mentions of their NERC systems and the gold oracle NERC mentions [15]. Their experiments with the HIPE data revealed that collective entity linking is also beneficial for this type of texts-in contrast to linking mentions separately.…”
Section: Participating Systemsmentioning
confidence: 99%
“…For NERC, they improved the non-neural CRF baseline system with additional features such as context tokens, date regex match, ASCII normalization of the focus token, and the 100 most similar words from the HIPE fastText word embeddings provided by the organizers. For EL, a knowledge-base driven approach was applied to disambiguate and link the mentions of their NERC systems and the gold oracle NERC mentions [15]. Their experiments with the HIPE data revealed that collective entity linking is also beneficial for this type of texts-in contrast to linking mentions separately.…”
Section: Participating Systemsmentioning
confidence: 99%
“…A handful of measures rely on RDF KBs [1,18,15,3,25,9]. Such KBs model both data (facts) and knowledge (ontological description of the application domain) using explicit and implicit triples; the latter can be derived through reasoning based on an RDF-specific consequence relation, a.k.a.…”
Section: Related Workmentioning
confidence: 99%
“…In the sequel, we chose to rely on WSRM to capitalize (i) on properties (R1) and (R2) that WSRM verifies and (ii) on its state-of-the-art performance for collective entity linking, in particular w.r.t. Ref [9].…”
Section: The Path-based Weighted Semantic Relatedness Measurementioning
confidence: 99%
See 2 more Smart Citations